Expression of aquaporins 3 in low grade risk of recurrence primary bladder cancer. Issue 3 (August 2021) - Ticonosco, Marco; Assumma, Simone; Iseppi, Andrea; Benedetti, Mattia; Sarchi, Luca; Ferrari, Riccardo; Calcagnile, Tommaso; Rocco, Bernardo; Sighinolfi, Maria Chiara; Alriyalat, Sulieman; Reggiani Bonetti, Luca; Migaldi, Mario; et al.
Introduction: Bladder cancer (BC) is one of the most frequent malignancy of the urinary tract. Recent studies demonstrated the role of aquaporins urothelial tumor cells (AQPs) as potential prognostic factor for tumor progression and invasion. In this study we investigated the AQP3 expression levels inside primary superficial (pTa) low grade bladder cancer, correlating with pathological parameters and clinical outcomes. Materials and methods: We retrospectively analyzed tumor samples of 66 patients with diagnosis of superficial urothelial (pTa) bladder cancer between 1997 and 2007. All patients underwent transurethral bladder resection (TURB ) and immediate single instillation of mitomycin C . All tumors samples were blindly reviewed by two expert anatomopathologists and only pTa low grade urothelial bladder cancer were included. Cancer recurrence was defined as the detection of bladder lesions during follow-up cystoscopy. AQP3-immunoreactive areas detected at immunohistochemical analysis were classified as AQP3 positive. Results: Of these 60.6% of patients was detected as negative for AQP3 expression. Forty-two patients develop cancer recurrence during follow-up with a mean progression free survival of 16.44 months. The absence of reaction for AQP3 was observed 56% (9/16) tumor grading G1 and 62% (31/50) tumor grading G2. No correlation was observed with sexual gender, grading of tumor differentiation, and recurrence of cancer disease. Kaplan-Meier curves of disease-free survival (DFS) showed a significant separation ( p = 0.028) between patients AQP3-positive and AQP3-negative. It was observed a mean DFS of 23.83 and 14.43 months respectively in absence and presence of AQP3 expression. Conclusion: AQP3 expression is related to disease-free interval (DFI) and the absence of AQP3 expression correlates with a late relapse. The expression of AQP3 does not provide a reproducible quantitative aspect. AQP3 are not suitable to forecast tumor cell behavior but they perform a role as regulator for tumor cell homeostasis and for additional therapeutic developments.